Endoscopic closure of refractory esophageal fistula after esophagectomy using polyglycolic acid sheets: a pilot study - Nagami, Yasuaki; Ominami, Masaki; Sakai, Taishi; Fukunaga, Shusei; Tanaka, Fumio; Taira, Koichi; Tanigawa, Tetsuya; Lee, Shigeru; Watanabe, Toshio; Fujiwara, Yasuhiro (Endoscopy International Open, 2020)
Background and study aims Esophageal fistulas after esophagectomy are associated with high mortality and poor quality of life. They are sometimes intractable to conservative management and surgery that increases mortality. Few studies have assessed use of polyglycolic acid (PGA) sheets with fibrin glue for esophageal fistulas. We investigated the safety of using PGA sheets with fibrin glue for esophageal fistulas after esophagectomy.Patients and methods This was a single-center prospective pilot study. Patients who had refractory esophageal fistulas after esophagectomy were included. PGA sheets were filled in the fistula using biopsy forceps. Fibrin glue was applied to the PGA sheets. We repeated the procedure 1 week later. The outcome measures were the incidence of adverse events (AEs) and closure of the fistula.Results Five patients were assessed. No adverse events were observed. The esophageal fistula was closed with the application of PGA sheets four times in 40 % (2/5) of the cases. Conclusions PGA sheets with fibrin glue were safe for esophageal fistula closure after esophagectomy and do not involve the risk of AEs.